Psychiatric Diagnoses Differ Considerably in Their Associations With Alcohol/Drug-Related Problems Among Adolescents. A Norwegian Population-Based Survey Linked With National Patient Registry Data - Heradstveit, Ove; Skogen, Jens Christoffer; Hetland, Jørn; Stewart, Robert; Hysing, Mari (Frontiers in Psychology, 2019)
The aim of this study was to examine alcohol/drug use and problems across psychiatric diagnoses and to what extent associations between each psychiatric diagnosis and alcohol/drug use and problems were independent from the potential confounding effects of psychiatric comorbidity, socioeconomic status, sex and age. We used a dataset comprising a linkage between a large population-based and cross-sectional study among Norwegian adolescents (the youth@hordaland conducted in 2012) and national registry-based data on specialist mental health care use during the four years prior to the survey (2008 to 2011). The study sample included 16 to 19 year olds who participated in the youth@hordaland survey and consented to the linkage with patient registry data (n=9,408). Among these, 853 (9%) had received specialist mental health care and comprised the clinical group, while the rest (n=8,555) comprised the comparison group. The main outcome variables were several self-reported indicators for alcohol/drug use, including any alcohol use, frequent alcohol intoxication, high-level alcohol consumption, and lifetime illicit drug use, as well as one indicator for potential alcohol/drug-related problems: a positive CRAFFT-score. Adolescents receiving specialist mental health care (n=853) reported more frequently alcohol/drug use and problems compared to adolescents not receiving these services (Cohens d’s ranging from 0.09 to 0.29, all p≤0.01). Anxiety, depression, conduct disorders, eating disorders, ADHD, and trauma-related disorders were all associated with single measures of alcohol/drug use and problems, with odds ratios (ORs) ranging from 1.58 to 4.63, all p<0.05) in unadjusted models. Trauma-related disorders, depression and conduct disorders were also positively associated with higher scores on a combined indicator of alcohol/drug use and problems (ORs ranging from 1.89 to 3.15, all p<0.01), even after the full adjustment from psychiatric comorbidity and sociodemographic variables (adjusted odds ratios ranging from 1.61 to 2.79, p<0.05). These results suggest that alcohol/drug use and problems were slightly more common among adolescents who received specialist mental health care during the past four years compared with the general adolescent population, and adolescents with trauma-related disorders, depression and conduct disorders were high-risk groups for alcohol/drug use and problems.